Global market conditions and systemic risk - González-Hermosillo, Brenda; Hesse, Heiko (IMF working paper, 2009)
This paper examines several key global market conditions, such as a proxy for market uncertainty and measures of interbank funding stress, to assess financial volatility and the likelihood of crisis. Using Markov regime-switching techniques, it shows that the Lehman Brothers failure was a watershed event in the crisis, although signs of heightened systemic risk could be detected as early as February 2007. In addition, we analyze the role of global market conditions to help determine when governments should begin to exit their extraordinary public support measures.